Perbandingan asupan makronutrien antara anak obesitas dengan normal pada siswa kelas 4-6 di Sekolah Dasar Santo Yoseph 2 Denpasar tahun 2017 - Ni Kadek Parswa Diah Pradnyandari; Wayan Weta; Anak Agung Sagung Sawitri (DiscoverSys Inc., 2019)
Background: Childhood obesity is a disturbance of nutritional status in children with body mass index per age (BMI / U) exceeding> 1 standard deviation (SD) - 2 SD followed by unbalanced diet between intake and output accumulated in excess fat storage. There are some related factors for obesity such as unbalanced diet, lack of physical activity, and the environmental agents.Aim: This research aims to find out the correlation between macronutrient intake with child obesity in grade 4-6 students at Santo Yoseph 2 Denpasar Elementary School.Method: The study was an analytical cross-sectional design with 60 samples obtained from random sampling technique and interviewed with questioner (SQ-FFQ) and then measured the height and weight in the period March-August 2017. Those interview data was processed with Nutriesurvey9Â© and analyzed with SPSS.Result: 60 samples showed the dominant child obesity occurred in male gender (70.0%). The proportion of child obesity by age group was highest at 10-12 years (51.2%). Analysis of the relationship of macronutrient intake with child obesity was obtained for energy intake (p = 0.007), protein (p = 0.009) and fat (p = 0.018) intake was p < 0.05, while carbohydrate (p= 0.074) p > 0.05.Conclusion: This study shows that there is a statistically significant relationship between energy intake, protein, and fat with child obesity. Reversely, carbohydrates, there is no statistically significant association with childhood obesity.